Compensation For Land Affected By Public Road Construction In Deli Serdang Regency - Bagus Owen (International Asia Of Law and Money Laundering, 2022)
Before the land is used for public purposes such as roads, markets and others can be implemented through the procedures established by law is no exception to the acquisition of land destined for private interests. In land acquisition can be done as stipulated in Article 21 of the basic agrarian law. To do land acquisition, the land must have a person or legal entity that owns it. In the land acquisition, a person or legal entity has the right to receive monetary compensation or replacement of land located elsewhere. In addition, the land acquisition required the approval or agreement of both parties to be implemented by the committee that handles the so-called Land Acquisition Committee.